Pengaruh Profitabilitas, Operating Leverage, Ukuran Perusahaan dan Pertumbuhan Penjualan pada Struktur Modal - Yudiandari, Cokorda Istri Diah (E-Jurnal Akuntansi, 2018)
Capital structure is a financial decision related to the composition of corporate debt, preferred stock and common stock used by the company, managers must be able to raise capital, both from within the company and from outside the company efficiently. The problem of capital structure is an important issue for every company, because good bad corporate capital structure will have a direct influence on its financial position. The importance of determining the structure of capital because it can be a strong foundation for the company to run its production activities, and able to obtain optimal benefits for the company. The purpose of this research is to obtain empirical evidence of profitability, operating leverage, firm size and sales growth on the capital structure of banking companies listed in Indonesia Stock Exchange period 2013-2015. Determination of the sample using purposive sampling method where the determination of the sample is determined using the criteria of banking companies listed on the Indonesia Stock Exchange period 2013-2015 and banking companies that publish the financial statements in succession during the period 2013-2015, obtained 10 companies that meet the criteria in 3 Years of observation resulting in 30 samples. Hypotheses were tested using multiple linear regression analysis techniques. Based on the results of multiple linear regression analysis it is known that profitability and firm size have no effect on capital structure. However, operating leverage and sales growth have a negative and significant influence on capital structure. Keyword: Profitability, operating leverage, company size, sales growth, capital structure